Stimulation of leptin secretion by insulin - Tsai, Minglun (Medknow Publications & Media Pvt Ltd, 2012)
Leptin has a crucial role in regulating food intake and maintaining metabolic homeostasis. Although little is known about the process of leptin secretion, insulin, which has an important role in the metabolism of glucose and lipids, is believed to regulate leptin secretion through a posttranscriptional mechanism in the short term, and via glucose metabolism in the long term. The gastric mucosa secretes leptin, but this mechanism has not been completely elucidated. Understanding the mechanism of insulin-regulated leptin secretion could lead to the development of new treatment methods for obesity and its comorbidities, which are serious public health concerns.